2005
DOI: 10.1007/s10654-005-2953-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Survey of Tourette Syndrome in Children and Adolescents in Wenzhou of P.R. China

Abstract: An epidemiological survey on Tourette syndrome (TS) in a developing country is relatively scarce. This study was conducted to investigate the prevalence and distribution of TS in children and juveniles aged 7-16 years in Wenzhou of P.R. China. A total of 9742 children and adolescents were included in this survey. Cross-sectional study with stratified-cluster sampling method was used. The prevalence of TS among school-age children was estimated to be an average of 0.43%. The ratio of male to female was 10.6 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 10 publications
6
31
0
1
Order By: Relevance
“…Regarding the 0.56% TS prevalence of Wang and Kuo, the 0.68% probable TS of Lanzi et al, and the 0.43% TS of Jin et al, we see that they report similar TS prevalence when comparing to our study 21,22,23 . The 0.56% TS prevalence of the Taiwanese study is close to our 0.52% TS prevalence for the same age range (6,499 students/34 TS).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Regarding the 0.56% TS prevalence of Wang and Kuo, the 0.68% probable TS of Lanzi et al, and the 0.43% TS of Jin et al, we see that they report similar TS prevalence when comparing to our study 21,22,23 . The 0.56% TS prevalence of the Taiwanese study is close to our 0.52% TS prevalence for the same age range (6,499 students/34 TS).…”
Section: Discussionsupporting
confidence: 78%
“…As being a one year prevalence study with 87% of their subjects having only one tic period, it implicates that these subjects should have had a more extended follow up period to categorize better TS subjects. Still, their CMTD to TS proportion (1.3% CMTD/0.5% TS) is too close.Regarding the 0.56% TS prevalence of Wang and Kuo, the 0.68% probable TS of Lanzi et al, and the 0.43% TS of Jin et al, we see that they report similar TS prevalence when comparing to our study 21,22,23 . The 0.56% TS prevalence of the Taiwanese study is close to our 0.52% TS prevalence for the same age range (6,499 students/34 TS).…”
supporting
confidence: 78%
“…Another characteristic of our study was that all TS patients were drug-naive and their clinical manifestations were much more obvious. In fact, an important factor that needs to be addressed here is, as in Taiwan [3], in China no public media of the general population have talked about TS until very recently, and the first epidemiological study in China was reported in 2005 [1]. Therefore, many TS children with motor tics such as blinking and vocal tics such as throat clearing are neglected as mischief making at first, and when they seek consultations from doctors the symptoms could be much severer.…”
Section: Discussionmentioning
confidence: 99%
“…Once considered as an extremely rare disorder, recent estimates of TS prevalence are approximately 4-6 per 1000 children [1][2][3][4]. From the largest international database of 3500 TS patients, Freeman et al [4] reported the mean male to female ratio to be 4.3:1, although wide variations among different international sites existed.…”
Section: Introductionmentioning
confidence: 99%
“…TS is typically treated by blocking dopamine receptors using antipsychotic drugs, among which is sulpiride, a selective dopamine D 2 antagonist, which is the most effective for pediatric formulation (3). Having this case, there is a lack of pediatric products of sulpiride that can fulfill the needs of the developing countries, where TS is mostly prevalent among children and juveniles (4). In particular, there is a formulation that can be administered by unqualified personnel who cannot administer oral products ("non-per os") to children.…”
Section: Introductionmentioning
confidence: 99%